Teacher's Perceptions of the Implementation of the Educational Process in the Context of Inclusive Education for Children with Disabilities in Russia - I.N. Nurlygayanov; S.B. Lazurenko (Психологическая наука и образование)
The paper presents the results of the analysis of the empirical research of teachers' opinion about the status of inclusive education in the Russian Federation. The comparative analysis was focused on the answers of teachers of special (correctional) schools (N=192), teachers working in an inclusive format (N=210) to the questions of the author's questionnaire regarding professional training and work experience, ideas about the compliance of inclusive education with the special educational needs of schoolchildren with disabilities, existing problems in the implementation of the pedagogical process and ways to overcome them, the prospects for the implementation of inclusive education. It was revealed that the opinion of teachers working in educational organizations with different models of education for children with disabilities have both common positions and specific ones. Differences to a greater extent concern the expediency of spreading inclusive education for a number of psychological and pedagogical categories of children due to the presence of significant psychological difficulties and low performance of the educational process at high cost.